SEXUAL EDUCATION “CEKER (CEGAH KEKERASAN) DENGAN TANGKIS” METHOD IN PREVENTING SEXUAL VIOLENCE IN EARLY CHILDHOOD AT TUNAS BANGSA KINDERGARTEN, KEDIRI CITY - Sutik; Yoyok Febrijanto; Erva Elli K; Maria Anita Yusiana (Pedagogic Research-Applied Literacy Journal, 2024)
Early childhood is an age that is vulnerable to crime and sexual violence. Educational steps through sex education programs, children introduce to from an early age. Therefore, parents required to have sensitivity, skills, and understanding to be able to provide certain portions of information, which does not make children confused and curious because parents are the party most responsible for children in educational matters, including sex education. Accompanying children by parents, teachers, or people closest to them is especially important. The method used is to provide direct education by presenting material and animated videos. Measuring children's understanding uses a questionnaire with pictures, numbers, and letters. The results obtained showed that education was proven to be able to improve children's experience, with pre-test scores on children's understanding out of 30 children showing that 15 children (52%) were good, 11 children (36.7%) were sufficient, and 4 children (13.3%) were poor. , while the post-test scores of 30 children showed good understanding for 26 children (85%) and enough for 4 children (15%).